2023
DOI: 10.1039/d2cp03503k
|View full text |Cite
|
Sign up to set email alerts
|

Photo-oxidation reaction of tert-butyl chloride with OH radicals and Cl atoms in the troposphere and its implications

Abstract: In the present work, the temperature-dependent kinetics for the reaction of tert-butyl chloride (TBC) with OH radicals and Cl atoms were determined experimentally between 268 and 363 K, and theoretically...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…[79][80][81] During the atmospheric oxidation process of other VOCs, some studies have demonstrated that the high oxidation ability of the Cl radical leads to comparable, and in certain cases, higher rate constants in comparison to the OH radical. 79,[82][83][84][85][86][87][88][89][90] Nevertheless, the importance of the reactions between amines and Cl radicals has not been duly recognized, and related investigations into their reaction kinetics are still insufficient. Additionally, O 3 is also a highly reactive oxidant in the atmosphere, and it is reported that the degradation of ambient amines initiated by O 3 is also an important oxidation pathway in the stratosphere or where the O 3 pollution is serious.…”
Section: Atmospheric Chemistrymentioning
confidence: 99%
“…[79][80][81] During the atmospheric oxidation process of other VOCs, some studies have demonstrated that the high oxidation ability of the Cl radical leads to comparable, and in certain cases, higher rate constants in comparison to the OH radical. 79,[82][83][84][85][86][87][88][89][90] Nevertheless, the importance of the reactions between amines and Cl radicals has not been duly recognized, and related investigations into their reaction kinetics are still insufficient. Additionally, O 3 is also a highly reactive oxidant in the atmosphere, and it is reported that the degradation of ambient amines initiated by O 3 is also an important oxidation pathway in the stratosphere or where the O 3 pollution is serious.…”
Section: Atmospheric Chemistrymentioning
confidence: 99%